Fetal Tuberous Sclerosis: Sirolimus for the Treatment of Fetal rhabdomyoma. (3rd September 2022) - Dagge, Ana; Silva, Luísa Andrade; Jorge, Sofia; Nogueira, Estela; Rebelo, Mónica; Pinto, Luísa
Abstract: Background: Sirolimus constitutes a safe and effective treatment for cardiac manifestations of tuberous sclerosis complex (TSC) in children but only four cases describing prenatal treatment of rhabdomyomas with mTOR inhibitors have been published. Case: In this case, sirolimus was initiated at 26 weeks´ gestation in a pregnant woman with TSC with a fetus with a large rabdomyoma conditioning severe arrythmia. There was a significant reduction in the tumor size with ongoing treatment and a partial reversion of the arrythmia. Conclusion: m-TOR inhibitors can be considered for severe cases of fetal rhabdomyomas with poor prognosis given its potencial benefits.